Complex impacts of gallstone disease on metabolic syndrome and nonalcoholic fatty liver disease - Lyu, Jingting; Lin, Qinghong; Fang, Zhongbiao; Xu, Zeling; Liu, Zhengtao (Frontiers in Endocrinology, 2022)
Background: Patients with gallstone disease (GSD) often have highly co-occurrence with metabolic syndrome (MetS) and Nonalcoholic fatty liver disease (NAFLD) both associated with insulin resistance (IR). Meanwhile, highly prevalence of NAFLD was found in patients who received cholecystectomy. However, the associations of GSD with MetS, NAFLD is inconsistent in the published literature. And risk of cholecystectomy on NAFLD is unclear. Methods: We searched the PubMed, EMBASE and ISI databases for literature that met our study topic. To be specific, studies with focus on associations between GSD and MetS/NAFLD, and risk evaluation on cholecystectomy and NAFLD incidence were enrolled for further analysis. The random effect model was used to calculate the combined relative ratio (RR) and 95% confidence interval (CI). Results: Seven and six papers with focus on connections between GSD and NAFLD/MetS prevalence. Correspondingly, seven papers with focus on risk of cholecystectomy on NAFLD occurrence were also enrolled into meta-analysis. After pooling the results from individual study, patients with GSD had higher risk of MetS (RR:1.80, 95%CI: 1.45-2.24, P<0.05). Risk of GSD was increased by 21% in NAFLD patients. While, about 68% of increment on NAFLD prevalence was observed in patients with GSD (pooled RR: 1.68, 95%CI:1.60-1.76, P<0.05). With regard to individual MetS components, patients with higher systolic blood pressure were more prone to develop GSD, with combined SMD of 0.29 (96%CI: 0.24-0.34, P<0.05). Dose-response analysis found the GSD incidence was significantly associated with increased body mass index (BMI) (pooled OR: 1.02, 95%CI:1.01-1.03) in linear trends. Patients who received cholecystectomy had a higher risk of post-operative NAFLD (RR:1.69, 95%CI: 1.60-1.78, P＜0.05). And this impact was amplified in obese patients (OR: 4.18, 95%CI: 3.73-4.68, P=0.875). Conclusion: our results confirmed that controls on weight and blood pressure might be candidate therapeutic strategy for GSD prevention. And concerns should be raised on de-novo NAFLD after cholecystectomy.